Development and evaluation of an electronic algorithm using a combination of a two-step malaria RDT and other rapid diagnostic tools for the management of febrile illness in children under 5 attending outpatient facilities in Burkina Faso - Francois Kiemde; Adelaide Compaore; Fla Koueta; Athanase M. Some; Berenger Kabore; Daniel Valia; Toussaint Rouamba; Fadima Yaya Bocoum; Seydou Sawadogo; Macaire Nana; Diane Y. Some; Nadine A. Kone; et al. (Trials, 2022)
Abstract Background In Sub-Saharan Africa (SSA), febrile illnesses remain a major public health problem in children. However, the persistence of hrp2 antigen and the low sensitivity of pLDH RDT negatively affect antimalarials and antibiotics prescription practices. These limitations lead to poor management of febrile diseases and antimicrobial resistance (AMR). To improve the diagnosis of these febrile diseases and subsequent prescription of antimicrobials, it is hypothesized that the implementation of an algorithm including a two-step malaria RDT PfHRP2/pLDH supported by point-of-care (PoC) tests for bacterial infections could significantly improve the management of febrile diseases and thereby tackling AMR. Methods To assess the value of the proposed algorithm, an open-label randomized controlled trial with three arms, enrolling febrile children from 6 to 59 months is proposed. In the control arm, febrile children will be managed according to the Integrated Management of Childhood Illnesses (IMCI), which is part of the standard of care in Burkina Faso. Treatment will be done according to national guidelines. In the RDT decisional algorithm (RDT-DA) arm (intervention), the clinical examination based on IMIC will be supported by a two-step malaria RDT and bacterial infections RDTs. Prescription will be left to the discretion of the healthcare workers based on clinical examination and PoC test results. In the e-algorithm arm (intervention), artificial intelligence integrating multiple layers of clinical information such as clinical examination, signs/symptoms and medical history, and biological information such as biomarkers (CRP and WBC) and pathogen-specific PoC tests, and oximetry will be developed. The e-algorithm will serve to guide the diagnostic and management of febrile infections in children. In the 3 arms, the case report forms will be digitalized. A final follow-up visit (day 7) will be scheduled for all participants. Patients will be asked to come back to the health facilities before the scheduled visit if the symptoms persist or in case of health condition worsening. Discussion If successful, this study could contribute to improve the management of febrile diseases and reduce inappropriate use of antimicrobials. Trial registration The trial is registered at ClinicalTrial.gov, NCT05285657. Enrolment started on 4 March 2022 with long-term outcome being assessed completely by 2023.